Effect Of Cross Bred Cow Urine In Rat During Sub Acute Safety Study - Sanganal, Jagadeesh S.; kumar, Jaya; Tikare, Vinay; Jayaramu (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Acute and sub acute oral toxicity studies of Holstein Friesian cross bred cow urine was conducted to determine the median lethal dose for both male and female rats. There was no mortality even at the highest dose tested (5 ml/kg body weight) indicating that cow urine was practically non-toxic. In the repeated dose 28 day sub acute oral toxicity study the blood and serum samples were analyzed on day 0, 14 and 28 for estimating different hematological parameters (TEC, TLC, DLC, Hb, Hct, MCV, MCH and MCHC). There were significant (P<0.01) changes in hematological values as well as concentration of various hematological parameters, but the values were under normal ranges.